1992
DOI: 10.1139/m92-062
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase polymerase chain reaction: applications for direct detection of enteric pathogens in waters

Abstract: The techniques in current use for detection of pathogens in environmental samples are restricted to those organisms whose replication in either culture media or cell culture is feasible. These methods lack the selectivity and sensitivity necessary for their unequivocal detection and identification. We have developed an assay for the detection of bacterial cells in large volumes of water. Low concentrations of cells containing target sequences were concentrated on membrane filters and were subjected to amplific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Bej et al (1991a) reported that PCR was not inhibited by the presence of PTFE and polyvinylidene difluoride filters, with PTFE giving the greatest sensitivity, but was inhibited by polycarbonate, nitrocellulose, and cellulose acetate filters. Both Nytran (Alvarez et al 1994) and nitrocellulose (Toranzos and Alvarez 1992) filters have been successfully used in solidphase PCR, where cell lysis and PCR amplification are performed on the membrane.…”
Section: Concentration and Filter Elutionmentioning
confidence: 99%
“…Bej et al (1991a) reported that PCR was not inhibited by the presence of PTFE and polyvinylidene difluoride filters, with PTFE giving the greatest sensitivity, but was inhibited by polycarbonate, nitrocellulose, and cellulose acetate filters. Both Nytran (Alvarez et al 1994) and nitrocellulose (Toranzos and Alvarez 1992) filters have been successfully used in solidphase PCR, where cell lysis and PCR amplification are performed on the membrane.…”
Section: Concentration and Filter Elutionmentioning
confidence: 99%
“…Microparticles come in all shapes and sizes, from soft spheres to porous structures to irregularly shaped rocks, in paramagnetic or non-magnetic varieties. Relative to the entire bio/chemical process, however, we find that microparticles are also compatible with each of the functions outlined in Figure 1: whole cell concentration (29,30), cell lysis (31), nucleic acid purification (32), solidphase PCR amplification (33), and detection (34)(35)(36). This is not to say that a particle (or more generally, a reactive surface) is required to perform each of the functions involved in any particular biodetection process, only that many of the selective chemistries and functional attributes required to complete innumerable biodetection processes are compatible with microparticle-based systems and selective-chemistry.…”
Section: Bio/chemistrymentioning
confidence: 76%
“…154,155 In recent years, the use of immunomagnetic beads attached to specific antibodies have become a popular approach in facilitating the capture, concentration, and purification of target bacteria prior to DNA extraction. 156 Several assays based on the direct detection of indicator and pathogenic bacterial cells in environmental water samples by filtration and PCR [157][158][159][160] have been developed. The use of combinations of methods such as immunomagnetic capturing of strains, PCR, and detection of immobilized amplified nucleic acids by hybridization have been proven to be useful for the detection of waterborne pathogenic bacteria that are difficult to culture from environmental sources, for example, Y. enterocolitica, 161,162 and H. pylori.…”
Section: Nucleic Acid-based Detection Methodsmentioning
confidence: 99%